Introducing Probabilities and Present Value Analysis into Taxation. - Crumbley, D. Larry (The Accounting Review, 1972)
Abstract This article discusses the use of probabilities and present value analysis in the taxation of lifetime gifts in the U.S.. Probabilities and present value analysis are used frequently in accounting literature and solutions to accounting problems. In the teaching of tax accounting, however, both the use of probabilities and present value analysis has received limited acknowledgement. Teachers should devise tax problems that will lead students to consider both of these concepts when working tax problems. Assume that a discount rate of 5 percent is adequate and that the property does not appreciate or depreciate during the period of time between the date of gift and date of death of the donor. Further, life expectancy data is obtained from actuarial tables provided by the Treasury Department. But the gift and estate taxes are often not the only tax considerations, for the income tax may be an important variable. If the gift property is income-producing property, there can be a sizeable overall income tax saving if the donee is in a lower income tax bracket than the donor.